Pengujian moderasi inflasi pada pengaruh profitability, financing to deposit dan capital adequacy ratio terhadap risiko pembiayaan - Iswandi, Iswandi; Ruhadi, Ruhadi; Setiawan, Iwan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of micro variables (ROA, FDR, and CAR) as well as the total variable in the form of inflation as a moderating variable on NPF in Indonesian Islamic commercial banks for the 2016-2020 period. The data analysis method used is explanatory and is a research that uses the type of assessment of causality between the variables studied (causal relationship). The theory used is agency theory. With regard to the relationship between the principal and the agent, the agent appointed by the principal or appointed to manage the services of the company's activities must be in good health. The result to be achieved is that the inflation variable is able to become a moderating variable for certain factors on non-performing financing (NPF) in Islamic commercial banks in Indonesia. The results of the analysis show that directly Capital Adequacy Ratio (ROA) and Capital Adequacy Ratio (CAR) have a significant negative effect on Non Performing Financing (NPF) while Financing to Deposit Ratio (FDR) has no effect on financing (NPF). In addition, the Capital Adequacy Ratio (ROA) also has an indirect effect on Non Performing Financing (NPF) and Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR) does not moderate the Non Performing Financing (NPF).